LALOUETTE, Jacqueline. 2018. Un peuple de statues. La célébration sculptée des grands hommes (France 1801-2018). Paris: Mare et Martin. - Joris Lehnert (apropos [Perspektiven auf die Romania], 2020)
Rezension